You are on page 1of 18

# DISTRIBUTION OF PRIMES

M. N. G. EINSTEIN

Abstract. In this paper we expand the prime number theorem, twice. Then
we use both expansions to describe the distribution of primes. Afterwards we
analyze the symmetry in the asymptotic equivalence. At last we come to the
solution of the zeros of the ζ−function.

Contents
1. Expansion of the Prime Number Theorem 1
2. Visualisation of the Distribution of Primes 3
3. Distribution of Primes 5
4. Conformation 6
5. Symmetry in Prime Distribution 7
6. Zeros of the ζ−function 8
7. Computing the non trivial zeros 10
8. Closing Argument 12
9. Proving the equivalence 15
References 18

## 1. Expansion of the Prime Number Theorem

Theorem 1.1. For all R+ 3 k ≥ 1 it is:
π(x)
lim   = k
x→∞ x
π
k
Proof. After the prime number theorem we have:
   
x x x
k log k log
log(x) x k k
lim x = lim = lim =
x→∞   x→∞ log(x) x x→∞ log(x)
x
k log
k

## k log(x) − k log(k) k log(x) k log(k)

= lim = lim − =k
x→∞ log(x) n→∞ log(x) log(x)

1
2 M. N. G. EINSTEIN

## Theorem 1.2. Let x0  x. Then for all N+ 3 n ≥ 1 it is:

(n−1)
π(x) x0 n

lim 1 =
x→x0 π(x n ) n
Proof. After the prime number theorem we have:
x
log(x) x0 n1 log(x0 ) 1 x0
lim x = 1 = n 1 =
x→x0 log(x0 ) x0n x0n
1
log(x n )
(n−1)
1− 1
x n x0 n

= 0 =
n n


This yields in total:
x
π(x) ∼
log(x)
(n−1)
1 x n
π(x) ∼ π(x n )
n
 
x
π(x) ∼ kπ
k
n 1
π(x) (n−1)
∼ π(x n )
x n

 
π(x) x
∼ π
k k
DISTRIBUTION OF PRIMES 3

## 2. Visualisation of the Distribution of Primes

After the expansion of the prime number theorem we have:
 
π(x) x
∼π
k k
which is equivalent to:
]|P| ≤ x x
∼ ]|P| ≤
k k

## To clarify the circumstances of that statement, let k ∈ N, then we get:

]|P| ≤ x x
∼ ]|P| ≤
2 2
]|P| ≤ x x
∼ ]|P| ≤
3 3
]|P| ≤ x x
∼ ]|P| ≤
4 4
.. .. ..
. . .

This sequence shows, that half (one third, one fourth, . . . ) of the prime numbers
lie in half (one third, one fourth, . . . ) of x. But this means, that the prime numbers
are as uniformly distributed as possible. Hence, we can conclude, that the expansion
of the prime number theorem proves already the Riemann hypothesis. For k = 2
y

 
π(x) x
∼π
2 2
π(x)

]|P| ≤ x ]|P| ≤ x
2 2

0 x→∞
 
x x
π = ]|P| ≤
2 2
4 M. N. G. EINSTEIN

which yields:
Zx Zx/2
]|P| ≤ x 1 dt dt x
∼ ∼ ∼ ]|P| ≤
2 2 log(t) log(t) 2
2 2
While the left hand side counts for half of all the primes in the interval [2, x], the
x
right side counts all primes in the interval [2, ]. Hence, we can conclude that half
2
x
of all the primes in the interval [2, x] lie in the interval [2, ]. We can continue
2
this sequence of course, which results in:
Zx Zx/2
1 dt dt

2 log(t) log(t)
2 2

Zx Zx/3
1 dt dt

3 log(t) log(t)
2 2

Zx Zx/4
1 dt dt

4 log(t) log(t)
2 2

.. .. ..
. . .

We point out, that not only the expansion of the prime number theorem −, but
also the established Mertens matrix becomes visible. Further, it proves:
π(x) = li(x) + O(xϑ+ε )
with 12 ≤ ϑ < 1 and ε > 0, which is equivalent to the Riemann hypothesis, since
π(x) ∼ li(x) ⇒ π(x) = li(x) + y, but y = O(xϑ+ε ) → 0. This is very easy to show,
if we claim:
x
+ xϑ+ε
log(x)
lim x =1
x→∞
log(x)

this yields:
"  # " #
x log(x) x log(x) log(x)
lim + xϑ+ε = lim + 1−ϑ−ε =1
x→∞ log(x) x x→∞ x log(x) x
| {z } | {z }
→1 →0
DISTRIBUTION OF PRIMES 5

3. Distribution of Primes
Theorem 3.1. Prime numbers are as uniformly distributed as possible.
Proof. After the explicit formula we have:
∞ 1 Z ∞
X π(x n ) X
ρ 1−ρ
 du
π(x) + = li(x) − li(x ) + li(x ) + 2 − 1) log(u)
− log(2)
n=2
n ρ=β+iγ
u(u
γ>0 x

for any x ≥ 2. According to the prime number theorem we have for the prime
counting function:
x
π(x) ∼
log(x)
and for its expansion:
 
x 1 n
kπ ∼ π(x) and π(x n ) ∼ π(x) (n−1)
k x n
with which we get:
X π(x n1 ) X nπ(x) X π(x)
π(x) + ∼ π(x) + (n−1)
= π(x) + (n−1)
n
n=2 2≤n≤x x n n 2≤n≤x x n

whereby we have:
X π(x) X π(x) π(x) π(x) π(x) π(x)
π(x) + (n−1)
∼ (n−1)
∼ π(x) + 1 + 2 + 3 + 4 + . . .
2≤n≤x x n n≤x x n
x2 x3 x4 x5

This is the exact symmetry we have expected in order for the prime numbers
to be as uniformly distributed as possible. The same symmetry can be found in
the functional equation for the zeta function. How does this show that the prime
numbers are as uniformly distributed as possible?
Let us assume the following three different distributions:
" #
1 1 1
Ω1 (x) = A1 x 1 + x + x + x + . . .
2 4 6

" #
1 1 1
1
Ω2 (x) = A2 x + x + x + x + . . .
3 5 7

1
X
Ω3 (x) = A3 xn
comn

## whereby ∀i : Ai ∈ R+ . Ω1 (x) and Ω2 (x) describe a clear pattern and would

favour the one or the other side. Hence, they cannot describe an uniformly dis-
tribution. Ω3 (x) on the other hand would create gaps that are much to wide in
contradiction to Bertrand’s postulate (n < p < 2n). Therefore an uniformly distri-
1
bution can only be given by an equation that covers all x n as it is shown by the
explicit formula. Both expansions of the prime number theorem bring that only
forward and make it visible.
6 M. N. G. EINSTEIN

4. Conformation
Riemann gave the following formula in terms of the related prime counting func-
tion:
1 1 1 1 1 1 1 1
Π(x) = π(x) + π(x 2 ) + π(x 3 ) + π(x 4 ) + π(x 5 ) + . . .
2 3 4 5
After the second expansion of the prime number theorem, we have:
n 1
π(x) (n−1) ∼ π(x n )
x n
which yields:
1 2 π(x) 1 3 π(x) 1 4 π(x) 1 5 π(x)
Π(x) ∼ π(x) + + + + + ...
2 x (2−1)
2 3 x (3−1)
3 4 x (4−1)
4 5 x (5−1)
5

## π(x) π(x) π(x) π(x) π(x) π(x)

∼ π(x) + 1 + 2 + 3 + 4 + 5 + 6 + ...
x2 x3 x4 x5 x6 x7

## but that is nothing more than:

1 1 1 1
x x2 x3 x4 x5
Π(x) ∼ + + + + + ...
log(x) log(x) log(x) log(x) log(x)
DISTRIBUTION OF PRIMES 7

## 5. Symmetry in Prime Distribution

We have found previously for:
∞ 1
X π(x n ) X
li(xρ ) + li(x1−ρ )

π(x) + = li(x) −
n=2
n ρ=β+iγ
γ>0

Z∞
du
+ − log(2)
u(u2 − 1) log(u)
x

## the asymptotic equivalence:

X π(x) X π(x) π(x) π(x) π(x) π(x)
π(x) + (n−1)
∼ (n−1)
∼ π(x) + 1 + 2 + 3 + 4 + . . .
2≤n≤x x n n≤x x n
x2 x3 x4 x5
for which we get, with π(x) ∼ x/ log(x), the following equation:
" #
1 1 1 1 1 1 X 1 X π(x)
x + x + x + x + ... =
2 3 4 xn ∼ (n−1)
log(x) log(x)
n≤x n≤x x n

We recognize the prime number theorem and both its expansions. Hence, we have:
1 X 1 X
li(xρ ) + li(x1−ρ )

x n ∼ li(x) −
log(x)
n≤x ρ=β+iγ
γ>0

Z∞
du
+ − log(2)
u(u2 − 1) log(u)
x
8 M. N. G. EINSTEIN

## 6. Zeros of the ζ−function

The asymptotic equivalence yields:
X π(x) X
li(xρ ) + li(x1−ρ )

(n−1)
∼ li(x) −
n≤x x n ρ=β+iγ
γ>0

Z∞
du
+ − log(2)
u(u2 − 1) log(u)
x

For x% we get:
Z∞
X π(x) X du
li(xρ ) + li(x1−ρ ) +

log(2) + ∼ −
x
(n−1)
n u(u2 − 1) log(u)
2≤n≤x ρ=β+iγ
x
γ>0
| {z }
→0+

Hence, we have found an asymptotic equivalence for the zeros of the Riemann
ζ−function.
We can rewrite the asymptotic equivalence:
Z∞
X π(x) X du
li(xρ ) + li(x1−ρ ) +

log(2) + ∼ −
x
(n−1)
n u(u2 − 1) log(u)
2≤n≤x ρ=β+iγ
x
γ>0
| {z }
→0+

to: " #
1 1 1 1
log(2) + x + x + x + ...
2 3 4
log(x)
which is quite similar to the equation we have found prior:
" #
1 1 1 1 1 X 1 X π(x)
x1 + x 2 + x 3 + x 4 + . . . = xn ∼ (n−1)
log(x) log(x)
n≤x n≤x x n

Thus, we have found an equation that allows us to compute the zeros of the
Riemann ζ−function directly via the prime distribution.
DISTRIBUTION OF PRIMES 9

## Remark 6.1. We point out, that with equation:

" #
1 1 1 1
log(2) + x2 + x3 + x4 + . . .
log(x)
| {z }
∈R
we can conclude:
X
li(xρ ) + li(x1−ρ )


ρ=β+iγ
γ>0
| {z }
∈R

which means that all roots have to be real, meaning, the condition:
ξ(z) = ξ(1/2 ± it) = 0
for t ∈ R has to be fulfilled.
Remark 6.2. The asymptotic equivalence:
X π(x) X π(x) π(x) π(x) π(x) π(x)
π(x) + (n−1)
∼ (n−1)
∼ π(x) + 1 + 2 + 3 + 4 + . . .
2≤n≤x x n n≤x x n | x2 x 3 {z x 4 x5 }
:=π(ζ)

reveals why the values γ of the zeros ρ = β + iγ take such irrational forms. A short
n
analysis of π(ζ) shows, that the exponents x n+1 not only create a step function,
but also push the values towards their final form.
10 M. N. G. EINSTEIN

## 7. Computing the non trivial zeros

We want now to present a formula that allows us to calculate the non−trivial
zeros of ζ(z). On the basis of the already proven and derived equations, we get:
1 ρ
xn
X 1 Z Zx Zx Z∞
dt dt X dt du
∼ − − log(2) +
n log(t) log(t) ρ
log(t) u(u2 − 1) log(u)
n≤x 2 2 2 x

ρ
Zx Zx Zx Z∞
X 1 dt dt X dt du
n ∼ − − log(2) +
x n+1 log(t) log(t) ρ
log(t) u(u2 − 1) log(u)
0≤n≤x 2 2 2 x

due to:
1 1 1 1 1 1 1 1
π(x) + π(x 2 ) + π(x 3 ) + π(x 4 ) + π(x 5 ) + · · · =
2 3 4 5
Z∞
X
ρ du
= li(x) − li(x ) + − log(2)
ρ
u(u2 − 1) log(u)
x

We can expand the prime number theorem one more time, which yields:
1 1 1
π(x k )nx n − k
1
π(x ) ∼ n
k
The formula allows us now to verify the line of zeros. By inserting the expansion
into the asymptotic equivalence we get with k = 2:
1 ρ
Zx 2 Zx Zx Z∞
1 X 1 −1 dt dt X dt du
(7.05) xn 2 ∼ − − log(2) +
2 log(t) log(t) ρ
log(t) u(u2 − 1) log(u)
n≤x 2 2 2 x
or more appropriately:
1
!
π(x 2 ) 1 1 1 1 1 1 1 1 1 1
∼ π(x) + 1 + x3−2 + x4−2 + x5−2 + x6−2 + x7−2 + . . .
2
We recognise the symmetry in the prime distribution, we have encountered before,
and the construction rule of the Riemann ζ function within/via the logarithms; if,
1 1
in the sequence x n − k one exponent would be different or would even miss, then it
would not represent ζ(z). Of course it is possible to change k to any real number
≥ 1 (k ∈ R+ ), but due to the uniformly distribution of the prime numbers this is
only a different representation of the above asymptotic equivalence (since you can
transform them back via the expansion of the prime number theorem to the above
asymptotic equivalence).
DISTRIBUTION OF PRIMES 11

We can use now equation 7.05 to compute the zeros. Since the last integral on
the right hand side tends to zero and the first integral on either side is equal, we
can conclude:
1
Zx 2 xρ
1 X 1 −1 du XZ du
(7.07) xn 2 ∼− − log(2)
2 log(u) ρ
log(u)
2≤n≤x 2 2
We can rewrite the left hand side as follows:
1 1
x 2 (cos(t log(x))+i it log(x)
Z sin(t log(x))) x 2 eZ
1 X 1 −1 du 1 X 1 −1 du
xn 2 = xn 2
2 log(u) 2 log(u)
2≤n≤x 2 2≤n≤x 2

## For the above case (equation 7.07) we have t = 0 and σ = 12 , if z = σ + it with σ,

t ∈ R. But we can clearly see, that when t 6= 0, then the integrals start to oscillate.
1 −1
In order to get the zeros, we have to get rid of the front factor x n2 2 . Since σ is
predetermined and x increases, it only can go into t. Thus, if we solve (for n ≥ 2):
1 1
Zx 2 x 2 eiγ
Zn
log(x)
Zx
ρ

1 1 −1 du du du
xn 2 = ∼
2 log(u) log(u) log(u)
2 2 2

such as the asymptotic equivalence is fulfilled, we are actually solving for the
non−trivial zeros of ζ(z). Hence, we have established that the complete knowledge
of the primes is contained in the Riemann zeros and we have used the primes to
determine those exact zeros.
We can see the factor σ = 1/2 controls the oscillation as xσ is the amplitude. If
σ 6= 1/2, then we recognise that:
Zx Zx/k
]|P| ≤ x 1 dt dt x
∼ ∼ ∼ ]|P| ≤
k k log(t) log(t) k
2 2
would not hold anymore as the oscillation would either be amplified (σ > 1/2) or
abated (σ < 1/2) (in terms of the distribution of the primes this would mean, either
a gap would exist contrary to Bertrand’s postulate or a pattern would occur), which
after the prime number theorem and its expansions cannot be true.
To solve for the non−trivial zeros, we can use the left hand side, which we can
compute via the many series we have already established (we can use even the
left hand side of equation 7.07) and set it asymtotically equal to our asymptotic
equivalence. All that remains then, is to variate the γn , whereby we have the
condition: γ1 < γ2 < · · · < γn .
12 M. N. G. EINSTEIN

8. Closing Argument
For Re(z) > 1 we have:
!
X 1
log ζ(z) =
p
1 − p−z
after: Y 1
ζ(z) =
p
1 − p−z
With the integral:
Z∞
−nz
p =z x−z−1 dx
pn
we get for log ζ(z):
∞ ∞ ∞ ∞
p−nz
Z Z
XX XX 1
log ζ(z) = =z x−z−1 dx = z x−z−1 Π(x) dx
p n=1
n p n=1
n
pn 0

which yields:
Z∞ 1 1 1
!
x x2 x3 x4
log ζ(z) ∼ z x−z−1 + + + + ... dx
log(x) log(x) log(x) log(x)
0

Z∞ !
1 1 2 3
∼z x−z + x−z− 2 + x−z− 3 + x−z− 4 + . . . dx
log(x)
0

Hence, we have:
Z " Z∞
c+i∞ !#
1 1 1 2 3
Π(x) ∼ xz x−z + x−z− 2 + x−z− 3 + x−z− 4 + . . . dz
2πi log(x)
c−i∞ 0

which explains:
Z∞
X du
Π(x) = li(x) − li(xρ ) + − log(2)
ρ
u(u2 − 1) log(u)
x
With:
! !
X z z z
log ζ(z) = log 1 − − log(2) − log Γ 1 + + log(π) − log(z − 1)
ρ
ρ ρ 2
DISTRIBUTION OF PRIMES 13

we get, on the basis of the previous derivation, the following asymptotic equiva-
lence:
Z∞ 1 1 1
!
−z−1 x x2 x3 x4
z x + + + + . . . dx ∼
log(x) log(x) log(x) log(x)
0
! !
X z z z
log 1 − − log(2) − log Γ 1 + + log(π) − log(z − 1)
ρ
ρ ρ 2

## If we use the integral:

Z∞ " #∞ " #∞
−z−1 x−z −z
z x dx = z = x = p−nz
z n n
pn p p

## we can see, how the distribution of the primes determines:

Z∞ 1 1 1
!
−z−1 x x2 x3 x4
z x + + + +... dx ∼
log(x) log(x) log(x) log(x)
0 | {z } | {z } | {z } | {z }
∼π(x) π(x) π(x) π(x)
∼ 1 ∼ 2 ∼ 3
x2 x3 x4

log ζ(z), since the lower bound in the above integral changed from pn to zero.
For any x ≥ 2 we have the explicit formula:
∞ 1 Z ∞
X π(x n ) X du
li(xρ ) + li(x1−ρ ) +

π(x) + = li(x) − 2
− log(2)
n=2
n ρ=β+iγ
u(u − 1) log(u)
γ>0 x

If we substitute: X X 1 X 1
Π(x) := =
p pn <x
n pn <x n
in the left hand side, we get:
∞ ∞
!
X 1 X µ(n) 1
Π(x nk )
k n=1 n
k=1
which we can do after:

X µ(n) 1
π(x) = Π(x n )
n=1
n
whereby:
X π(x) X π(x) π(x) π(x) π(x) π(x)
π(x) + (n−1)
∼ (n−1)
∼ π(x) + 1 + 2 + 3 + 4 + ...
2≤n≤x x n
n≤x x n x 2 x 3 x 4 x5
yields:
1 1 1 ∞ ∞
x x2 x3 x4 X µ(n) 1 1 X µ(n) 1
+ + + + ··· ∼ Π(x n ) + Π(x 2n ) + . . .
log(x) log(x) log(x) log(x) n=1
n 2 n=1 n
14 M. N. G. EINSTEIN

We recognize on the right hand side the Mertens matrix with the exact same
behaviour we have encountered before for x → ∞ as the negative elements of the
first series are canceled out. After the definition of Π(x) we have expected the left
hand side of the asymptotic equivalence to turn out this way. But, since we have
derived the left − and the right hand side completely separate from each other, the
two expansions of the prime number theorem for the left − and the new Mertens
matrix for the right hand side, we can conclude with the formula:
Z∞
X
ρ du
Π(x) = li(x) − li(x ) − log(2) + 2 − 1) log(u)
ρ
u(u
x
that the proof for the Riemann hypothesis is complete.
DISTRIBUTION OF PRIMES 15

## 9. Proving the equivalence

Theorem 9.1. Let  > 0, n > 2. Then there exists some constant c such that:
|M (n)| ≤ cn1/2+
Proof. We begin with the equation:
π(bn/pi c)−i≤0   π(bn/δi c)−(i+1)≤0  
X n X n
M (n) = 1 − π(n) + (π − i) − (π − (i + 1)) + . . .
i=1
pi i=1
δi
     
n n n
n 2 3 p
∼1− +   − 1 +   − 2 + · · · + k1  − k1 −
log(n) n n n
log log log
2 3 pk1
     
n n n
6 10 δ
−   + 2 −   + 3 − · · · − k2  + (k2 + 1)+
n n n
log log log
6 10 δk2
    
n n n
30 42 σ
+   − 3 +   − 4 − · · · − k3  + (k3 + 2) − . . .
n n n
log log log
30 42 σk3

As n tends to infinity, we observe, that almost all linear elements, besides those
at the beginning of the sums in each row with odd numbers, will cancel each other
out. Hence we are left with:
     
n n n
n 2 3 p
M (n) ∼ − +   +   + · · · + k1  −
log(n) n n n
log log log
2 3 pk1
     
n n n
6 10 δ
−   −   − · · · − k2  +
n n n
log log log
6 10 δk2
     
n n n
30 42 σ
+   − 3 +   − · · · − k3  − . . .
n n n
log log log
30 42 σk3
16 M. N. G. EINSTEIN

## If we start to summarise the elements we are left with:

N1 N2 N3
M (n) ∼ − + − ...
D1 D2 D3
whereby the first numerator is:
       
n n n n
N1 = −n log log log · · · log +
2 3 5 pk1
       
n n n n
+ log(n) log log · · · log +
2 3 5 pk1
       
n n n n
+ log(n) log log · · · log +
3 2 5 pk1

+···+
       
n n n n
+ log(n) log log · · · log
pk1 2 3 pk1 −1

## and the first denominator:

       
n n n n
D1 = log(n) log log log · · · log
2 3 5 pk1
For the second numerator we have:
         
n n n n n
N2 = − log log log · · · log −
6 10 14 15 δk2
         
n n n n n
− log log log · · · log −
10 6 14 15 δk2
         
n n n n n
− log log log · · · log −
14 6 10 15 δk2

−···−
         
n n n n n
− log log log · · · log
δk2 6 10 14 δk2 −1

## while the second denominator is:

       
n n n n
D2 = log log log · · · log
6 10 14 δk2
DISTRIBUTION OF PRIMES 17

## We can continue this summary for the rest of N3 , D3 , N4 , D4 , . . . , all of which

we can compactify with the laws of logarithm. We start with the first numerator
N1 , thus we are getting:
   
n n
  n log · · · log 
n 3 pk1
N1 = − log +
2
| {z }
= a11
     
 n log n
· · · log
n 
+ log |n 2 3 p k
} +
1
{z
= a12
     
 n log n
· · · log
n 
+ log n 3 2 p k
} +
1
| {z
= a13

+···+
     
n n n
 log · · · log 
+ log n p k1
2 p k1 −1
| {z }
= a1k1
 
a12 a13 · · · a1k1
= log
a11

## while for the denominator we get:

     
n n n
  log log · · · log 
n 10 14 δk2
D1 = log
6
| {z }
= b1
If we summarise the rest, we get:
     
a12 a13 · · · a1k1 1
log log log a31 a32 · · · a3k3
a11 a21 a22 · · · a2k2
M (n) ∼ + + −. . .
log(b1 ) log(b2 ) log(b3 )
which we can compactify one last time to:
 log(b2 ) log(b3 )··· log(bk )  log(b2 ) log(b3 )··· log(bk )
a12 a13 · · · a1k1 a31 a32 · · · a3k3 · · ·!
log  log(b ) log(b )··· log(b )
1 3 k
log(b2 ) log(b3 )··· log(bk )
a11 a21 a22 · · · a2k2 ···
M (n) ∼  
log(b2 ) log(b3 )··· log(bk )
log b1
18 M. N. G. EINSTEIN

With:
elog(n) = n
we get the transformation:
1
log(n)
elog(n)/ log(m) =e log(m) = elog(n) log−1 (m) =

 log−1 (m) −1
= elog(n) = nlog (m)

## If we raise both sides to the exponent of e we can use the transformation on

M (n), with which we arrive at:
 log(b2 ) log(b3 )··· log(bk )  log(b2 ) log(b3 )··· log(bk )
1
a12 a13 · · · a1k1 a31 a32 · · · a3k3 · · · ! log(b t)
M (n)
e ∼  log(b ) log(b )··· log(b )
1 3 k
log(b2 ) log(b3 )··· log(bk )
a11 a21 a22 · · · a2k2 ···

whereby:  
log(b2 ) log(b3 ) · · · log(bk )
bt = b1
Thus, we have:
1/2+
lim |eM (n) | ≤ ecn
n→∞
1/2+
since the basis of |eM (n) | is a fraction, while for ecn it is the Euler constant,
which increases faster than every other power as a result of:
nr
lim n
n→∞ e
whereby r ∈ R. For r ≤ 0, which is our case, since:
1
lim =0
n→∞ log(n)

## the proof is trivial, while for r > 0 we have:

nr
= er log(n)−n
en

due to log(n) < n we then get:

r log(n) − n < r n − n
with which follows the statement − and the equation above as well.


References
[1] M. N. G. Einstein. Combinatorial Number Theory.
[2] M. N. G. Einstein. Combinatorial Algebraic Number Theory.